Fault-Tolerant Energy Management in Renewable Microgrids using LPV MPC. Issue 35 (2022) - Morato, M.M.; Marquez, J.J.; Zafra-Cabeza, A.; Bordons, C.; Normey-Rico, J.E.
Abstract: In this paper, we formalise a fault-tolerant control and mitigation strategy for the energy management of renewable microgrids. The scheme is composed of a Model Predictive Control (MPC) algorithm based on a Linear Parameter Varying (LPV) model for the microgrid energy dispatch. The MPC uses fault diagnosis information in order to correctly update the LPV microgrid model, while adapting the process constraints in consonance with the level and location of faults. We show how closed-loop stability is ensured with simple quadratic terminal ingredients, provided through LMI-solvable remedies. Nonlinear simulation results of a real microgrid benchmark are included to demonstrate the effectiveness of the approach.